Wage Gaps - Jus Semper, La Alianza Global; de Salarios Dignos, Observatorio Internacional (Revista Internacional de Salarios Dignos, 2020)
Manufacturing wage gaps for Group of Seven (G7) large economies and other selected economies, including "emerging" economies with available wage and PPP data (1996-2017)